Dichotomous and stable gamma delta T-cell number and function in healthy individuals. Issue 5 (19th May 2021) - Ou, Lingling; Wang, Huaishan; Liu, Qin; Zhang, Jie; Lu, Hezhe; Luo, Liangping; Shi, Changzheng; Lin, Shaoqiang; Dong, Liyun; Guo, Yeye; Huang, Lili; Zhu, Jinjin; et al.
Abstract : Background: Gamma-delta (γδ) T lymphocytes are primed to potently respond to pathogens and transformed cells by recognizing a broad range of antigens. However, adoptive immunotherapy with γδT cells has exhibited mixed treatment responses. Better understanding of γδT cell biology and stratifying healthy donors for allogeneic adoptive therapy is clinically needed to fully realize the therapeutic potential of γδT cells. Methods: We examine 98 blood samples from healthy donors and measure their expansion capacity after zoledronate stimulation, and test the migration and cytotoxic effector function of expanded γδT cells in 2D culture, 3D tumor spheroid and patient-derived melanoma organoid assays. Results: We find that γδT cell expansion capacity is independent of expansion methods, gender, age and HLA type. Basal γδT cell levels in Peripheral blood mononuclear cell (PBMC) correlate well with their expansion, migration and cytotoxic effector capacity in vitro. Circulating γδT cells with lower expression of PD-1, CTLA-4, Eomes, T-bet and CD69, or higher IFN-γ production expand better. γδT cells with central memory and effector memory phenotypes are significantly more abundant in good expanders. A cut-off level of 0.82% γδT cells in PBMC stratifies good versus poor γδT cell expansion with a sensitivity of 97.78%, specificity of 90.48% and area under the curve of 0.968 in a healthy individual. Donors with higher Vδ2 Index Score in PBMC have greater anti-tumor functions including migratory function and cytotoxicity. Conclusions: Our results demonstrate that the interindividual γδT cell functions correlate with their circulating levels in healthy donors. Examination of circulating γδT cell level may be used to select healthy donors to participate in γδT-based immunotherapies.